PENGARUH COST OF DEBT, LABA, PERSENTASE PERUBAHAN LABA, SHAREHOLDER’S EQUITY DAN UKURAN PERUSAHAAN TERHADAP PENGUNGKAPAN LAPORAN KEUANGAN PADA PERUSAHAAN TEXTILLE DAN GARMENT YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2011-2015 - Wati, Kristina; Subroto, Setyowati (PERMANA, 2016)
The purpose of this study was to determine the effect of cost of debt, profit, percentage change in earnings, shareholder's equity and firm size both partially and simultaneously on the disclosure of financial statements at the textille and garment companies listed on the Indonesia Stock Exchange in 2011-2015. This research method uses a quantitative approach. Data Collection Techniques used in this study are documentation methods. while the analysis of the data used is testing classical assumptions, multiple linear regression analysis, significant test individual parameters (statistical test t), simultaneous significance test (statistical test F) and coefficient of determination. Based on the results of the Individual Parameters test (t Test Statistic), it can be concluded that there is no significant effect of the cost of debt on financial statement disclosures. Based on the results of the calculation of the Individual Parameters test (Test Statistic t) it can be concluded that there is a significant effect of earnings on the disclosure of financial statements. Based on the results of the calculation of the Individual Parameters test (Test Statistic t) it can be concluded that there is no significant effect on the percentage of earnings changes to the disclosure of financial statements. Based on the results of the Individual Parameter test (Statistic Test t), it can be concluded that there is no significant influence of shareholder's equity on financial statement disclosures. Based on the results of the Individual Parameters test (t Test Statistic), it can be concluded that there is no significant effect on the size of the company on the disclosure of financial statements. Based on the results of the simultaneous influence test it can be concluded that there is a significant influence between the cost of debt, profit, percentage change in earnings, shareholder's equity and company size simultaneously on the disclosure of financial statements.Keywords: cost of debt, profit, earnings change percentage, shareholder's equity, company size, financial statement disclosure.